Chapter 3 European Imperialism, War, Strategic Commodities and Ecological Limits The Diffusion of Hemp in Spanish South America and Its Ghost Fibers - Díaz-Ordóñez, Manuel (Taylor & Francis, 2021)
history of the Americas